The venous angioarchitecture of sporadic cerebral cavernous malformations: a susceptibility weighted imaging study at 7 T MRI. Issue 2 (20th October 2012) - Dammann, Philipp; Wrede, Karsten H; Maderwald, Stefan; El Hindy, Nicolai; Mueller, Oliver; Chen, Bixia; Zhu, Yuan; Hütter, Bernd-Otto; Ladd, Mark E; Schlamann, Marc; Sandalcioglu, I Erol; Sure, Ulrich
Abstract : Background and purpose: To test the hypothesis that sporadic cerebral cavernous malformations (CCMs) are systematically associated with venous malformations (VMs) using susceptibility weighted imaging (SWI) at 7 Tesla (T) field MRI. Methods: A prospective unselected series of 20 patients with symptomatic or asymptomatic sporadic CCM diagnosed using 1.5 T MRI was additionally scanned using high resolution (250 µm 2 in-plane) SWI at 7 T MRI. Imaging data were analysed to examine the presence and formation of CCM associated venous vessel structures. Interobserver agreement was assessed using kappa statistics. Results: In the 20 patients harbouring 23 CCMs, a solitary or multiple venous drainage was found in all lesions. A 'typical' VM was found in seven lesions. In the other cases, associated abnormal venous structures were also depicted although they appeared structurally different. Excellent interobserver agreement was achieved (95% confidence interval 0.92 to 0.99). Conclusions: Our data support previous assumptions that sporadic CCMs are systematically associated with local venous abnormalities involving larger outflow vessels. However, the typical appearance of a VM was not confirmed in all cases. The role of the venous environment in the pathomechanism of CCMs remains unclear.